Gambaran Penanganan Inkontinensia Urine Pada Lansia Di Keluarga Di Wilayah Puskesmas Jepon Kabupaten Blora - Abidin, M. Zainal (Program Studi Keperawatan Blora, Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
ABSTRACTBackground: Urinary incontinence is a common health problem in the elderly. Even though the family feels ashamed, they think that something that naturally happens to the elderly does not need to be addressed. Urinary incontinence can cause various health, social, psychological problems and can reduce the quality of life of the elderly in the family.Purpose: This study aims to get an overview of the management of urinary incontinence in the elderly in families in the Jepon Community Health Center, Blora Regency.Research Methods: The design of this research is phenomenological qualitative, with explorative descriptive design. The data obtained was processed using the Collaizi technique, consisting of seven steps. The number of participants in this study were four elderly people aged ≥ 80 years.Results: The results show that there is a lack of knowledge about urinary incontinence, urinating anytime, anywhere and cannot be controlled, the lack of effective ways to prevent urinary incontinence, the lack of education about how to treat it from health workersConclusion: The need for socialization and counseling about urinary incontinence, prevention and care for the elderly in the family.